Iron-catalyzed ring-opening of cyclic carboxylic acids enabled by photoinduced ligand-to-metal charge transfer. Issue 14 (28th June 2022) - Tu, Jia-Lin; Gao, Han; Luo, Mengqi; Zhao, Lulu; Yang, Chao; Guo, Lin; Xia, Wujiong
Abstract : A decarboxylative ring-opening reaction of cyclic tertiary carboxylic acids via an iron-catalyzed photoinduced ligand-to-metal charge transfer (LMCT) process is herein reported. Abstract : A decarboxylative ring-opening protocol of cyclic tertiary carboxylic acids via iron-catalyzed photoinduced ligand-to-metal charge transfer (LMCT) is described. This reaction enables the preparation of 1, n -dicarbonyl compounds through the homolytic C–C bond cleavage of unstrained carbocyclic and heterocyclic ring systems. This method exhibits a lot of synthetic advantages including mild conditions, simple operation, and convenience of amplification. Mechanistic studies support the generation of peroxy radical species via oxygen capture followed by radical fragmentation.